A Comprehensive Study on the Zeros of the Two-Parameter Mittag-Leffler Function - Farnoosh Abooali; Aliasghar Jodayree Akbarfam (Sahand Communications in Mathematical Analysis)
The Mittag-Leffler function appears as an analytical solution of some fractional differential equations. The behavior of the zeros of the Mittag-Leffler function, especially their asymptotic distribution, plays a fundamental role in the study of eigenvalue problems. The goal here is to derive a different form of the higher-order asymptotic distribution of the zeros of the Mittag-Leffler function.